Gregory Herburger: capstone - Herburger, Gregory, artist (Colorado State University. Libraries, 2015)
The artist's statement: The pinhole technique is one of the earliest and most fundamental photographic processes, in which a pin-sized hole is used to focus light and expose an image directly onto film. I use this process to capture a duration of time in a single, two-dimensional image. I make long exposure photographs using a pinhole camera with available light in familiar, everyday situations. I have ventured into the public sphere-to places where people naturally congregate and locations with compelling architectural forms, all of which serve an individual purpose and are designed to accommodate a human presence. I am interested in the activity of pedestrians and people gathered in likeness and the way they interact with each other and the shared spaces they inhabit. My photographs encourage the recognition of the value of these places and the purpose they serve along with a new awareness of the people in the built environment around them.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: photo image making